2019
DOI: 10.1163/15718182-02704002
|View full text |Cite
|
Sign up to set email alerts
|

Does Situation Matter in Conceptions of Children’s Nurturance and Self-determination Rights?

Abstract: Recent work regarding children’s rights has advocated for research in non-Western settings and with participants who are ethnic/racial minorities. We addressed these issues through secondary analysis of interviews with 63 mixed-race South African children (9-, 11-, and 13-year olds) and their mothers. Participants’ responses to hypothetical vignettes depicting children’s nurturance and self-determination rights scenarios were coded using social cognitive domain theory and subsequently analysed with mixed-desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…endorsing the nurturance right to parental emotional availability significantly more than the nurturance right to protection. The variations in endorsements of specific nurturance and self-determination rights align with research finding variations in children's endorsements of rights in different scenarios(Gilles et al, 2019).We investigated the role of democratic competences in children's endorsements of rights. Research has highlighted a relationship between democratic environments and children's support for rights(Khoury-Kassabri & Ben-Arieh, 2009;To et al, 2017).…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…endorsing the nurturance right to parental emotional availability significantly more than the nurturance right to protection. The variations in endorsements of specific nurturance and self-determination rights align with research finding variations in children's endorsements of rights in different scenarios(Gilles et al, 2019).We investigated the role of democratic competences in children's endorsements of rights. Research has highlighted a relationship between democratic environments and children's support for rights(Khoury-Kassabri & Ben-Arieh, 2009;To et al, 2017).…”
mentioning
confidence: 58%
“…The low endorsements of freedom from excessive chores, a nurturance right, differs from previous research. For instance, Gilles et al (2019) found South African children endorsed freedom from excessive chores similarly to other nurturance rights. This variation may be due to the situation in which this right is embedded because it differs from that explored by Gilles and colleagues (2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children living under difficult social or political circumstances such as high crime contexts may be more vulnerable to rights violations, and their reasoning about rights can be influenced by these experiences. For example, a study of mixed-race South African children living in settings marked by high rates of violence (i.e., Cape Town, South Africa; South Africa Institute of Race Relations, 2004) found that participants were less likely to support participation rights and more likely to support protection rights compared to same-aged peers residing in less violent settings (Gilles et al, 2019;Ruck et al, 2011). Children's greater support for protection rights may be due to the setting in which the study took place.…”
Section: Children Living Under Difficult Circumstancesmentioning
confidence: 99%